IVAN FRANKO'S GERMAN HERITAGE IN FORMING INTERCULTURAL COMPETENCE OF FUTURE TEACHERS OF FOREIGN LANGUAGES - Nataliia Rokitska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with Ivan Franko's German heritage along with peculiarities of his intercultural activity, which is manifested in the poet's works aiming at the German-speaking readers, and translations of his works. Versatile activity of I. Franko was based on European values, which contributed to high level of spiritual assets inherent to Ukrainian nation. Just as important condition for forming intercultural competencies through professional training of future teachers of foreign languages is a culturologic component with value attitude to national and foreign cultures, so it is brought forward to use creatively of the writer and thinker of genious, Ivan Franko. Franko's Words are eternal and influence the minds of many people in Europe and the world. Franko was a great strategist of national culture. He set himself the task of making Ukrainian culture more European in general, attaching it to the themes and models of European and world literary process. German literary heritage of Franko should be viewed not only as an important facet of a prominent journalist, writer and scientist, an important means of rapprochement of peoples, mutual enrichment of cultures, but above all as a desire to educate native people, to awaken their national consciousness, to build their own state, and in this case, to form intercultural competence of future teachers, teachers of new generation.